Rational design of DNA nanostructures for single molecule biosensing - Raveendran, Mukhil (Nat Commun, 2020)
The ability to detect low concentrations of biomarkers in patient samples is one of the cornerstones of modern healthcare. In general, biosensing approaches are based on measuring signals resulting from the interaction of a large ensemble of molecules with the sensor. Here, we report a biosensor platform using DNA origami featuring a central cavity with a target-specific DNA aptamer coupled with a nanopore read-out to enable individual biomarker detection. We show that the modulation of the ion current through the nanopore upon the DNA origami translocation strongly depends on the presence of the biomarker in the cavity. We exploit this to generate a biosensing platform with a limit of detection of 3 nM and capable of the detection of human C-reactive protein (CRP) in clinically relevant fluids. Future development of this approach may enable multiplexed biomarker detection by using ribbons of DNA origami with integrated barcoding.